2015
DOI: 10.1039/c5nr05394c
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectricity at the molecular scale: a large Seebeck effect in endohedral metallofullerenes

Abstract: Single molecule devices provide a unique system to study the thermoelectric energy conversion at an atomistic level and can provide valuable information for the design of organic thermoelectric materials. Here we present a comprehensive study of the thermoelectric transport properties of molecular junctions based on C(82), Gd@C(82), and Ce@C(82). We combine precise scanning tunneling microscope break-junction measurements of the thermopower and conductance with quantitatively accurate self-energy-corrected fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…The sign and magnitude of the thermopower of the Sc 3 N@C 80 single‐molecule junction can be controlled by the applied pressure. Here, Sc 3 N inside the cage produces a resonance state around the Fermi level, whose energy, and thus the thermopower, is tuned by applying the mechanical force …”
Section: Electronic Property Of Single‐molecule Junctionsupporting
confidence: 54%
See 2 more Smart Citations
“…The sign and magnitude of the thermopower of the Sc 3 N@C 80 single‐molecule junction can be controlled by the applied pressure. Here, Sc 3 N inside the cage produces a resonance state around the Fermi level, whose energy, and thus the thermopower, is tuned by applying the mechanical force …”
Section: Electronic Property Of Single‐molecule Junctionsupporting
confidence: 54%
“…Fluctuation in the electronic properties of the single‐molecule junctions reflects the character of the metal‐molecule bonds at the interfaces, which enables us to study the molecular adsorption process on the metal electrodes. The electronic energy levels in single molecules are discretized and quantum effects can play an important role in thermoelectric transport for the single atom and molecule junctions . We describe the thermopower of the single atom and molecule junctions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Lee et al studied the thermoelectric properties of three fullerene derivatives (C82, Gd@C82, and Ce@C82). They found that the Seebeck coefficient for all three fullerene derivatives is negative (electron‐conduction).…”
Section: Thermoelectric Properties Of Molecular Junctionsmentioning
confidence: 99%
“…Fullerenes also exhibit negative Seebeck coefficients, ranging from À10 to À30 mV K À1 for C 60 14 to À33 mV K À1 for C 60 dimers 15 and up to À31.6 mV K À1 C 82 endohedral fullerenes. 16 The sign of the endohedral fullerene Sc3N@C 80 was shown to be sensitive to pressure, ranging from À25 mV K À1 to +25 mV K…”
mentioning
confidence: 99%